2009
DOI: 10.1080/15412550903049157
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, Systemic Inflammation and Body Weight in Relation to Lung Function Impairment—An Epidemiological Study

Abstract: Recent reports on the simultaneous occurrence of systemic inflammation and airflow obstruction are usually based on a highly selective patient population, but their importance warrants further evaluation in the general population. The objectives were to study the interrelationship between airflow obstruction, smoking, hypertension, obesity and CRP as a marker of systemic inflammation in a randomly selected sample of the general Icelandic population (n = 939). This study comprised 758 randomly selected men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 30 publications
5
48
2
2
Order By: Relevance
“…It was possible that systematic inflammation has played a role as PM 2.5 -induced inflammation has been reported to be higher among participants with higher BMI. 35 This finding has also been supported by animal experimental studies, 36 which showed that obese mice presented higher airway inflammation than normal-weighted mice.…”
Section: Discussionmentioning
confidence: 62%
“…It was possible that systematic inflammation has played a role as PM 2.5 -induced inflammation has been reported to be higher among participants with higher BMI. 35 This finding has also been supported by animal experimental studies, 36 which showed that obese mice presented higher airway inflammation than normal-weighted mice.…”
Section: Discussionmentioning
confidence: 62%
“…15 19-21 At the end of November 2004, of the 73 391 subjects ≥ 40 years of age living in the area, 939 subjects were randomly selected to participate (for details, see ref. 19). Altogether, 762 of the 939 eligible subjects (81.2%) responded.…”
Section: General Population Cohortmentioning
confidence: 99%
“…Effects of obesity on airway caliber and obstruction to air flow that were not merely explained by a mechanical effect on lung volume have been reported in a limited number of studies (e.g., Salome et al 2010). It is hypothesized that proinflammatory adipokines produced by adipose tissue may contribute to airway remodeling in obese persons (Margretardottir et al 2009; McClean et al 2008; Tkacova 2010). Circulating inflammatory markers and adipokines (e.g., soluble tumor necrosis factor receptor 1, adiponectin, leptin) were inconsistently associated with respiratory function in subjects with excess body weight (Lecube et al 2011; Thyagarajan et al 2010).…”
Section: Introductionmentioning
confidence: 99%